Do body-related shame and guilt mediate the association between weight status and self-esteem?. (May 2015) - Pila, Eva; Sabiston, Catherine M; Brunet, Jennifer; Castonguay, Andree L; O'Loughlin, Jennifer
Individuals who are overweight or obese report body image concerns and lower self-esteem. However, little is known about the mechanisms underpinning these associations. The objective of this study was to test body-related shame and guilt as mediators in the association between weight status and self-esteem. Young adult participants ( n = 790) completed assessments of self-esteem and body-related guilt and shame, and weight status indicators were measured by trained technicians. Findings from multiple mediation analyses suggest that body-related shame mediates the relationship between weight status and self-esteem. If replicated in longitudinal studies, these findings suggest that reducing body-related emotions may have important implications for improving self-esteem in clinical weight management.